Clinical Outcomes of Mesh Repair In Incisional Hernia at PMCH, Nawabshah - Habib-ur-Rehman, Shahnawaz Leghari, Shahida Baloch (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: to determine the outcomes of Mesh-repair and put forward the assertion for safe and effective repair with lowest recurrence rate. Methods: A total 66 adult patients underwent for mesh repair in midline incisional hernia at surgical unit-I of PMCH, Nawabshah from 2010 to 2015 were analyzed. Patients having more than one hernia, signs of infection, previous repair with mesh and co-morbidities were excluded. Patient demographic characteristics, operative details, pre and post-operative complications and recurrence were studied. Results: in this study, 40 females (60.6%) and 26 males (39.4%) with male to female ratio of 1:1.5 met the inclusion criteria. The patients underwent with onlay (30), inlay (22) and sublay (14) mesh repair. 27.27 % (18) of patients experienced early postoperative complication. While during follow-up period of 02 years, 8 patients developed recurrences (12.2%). Conclusion: With lacking advance resources at our part of world, open polypropylene mesh repair of incisional hernia still remains to be safe and effective to avoid the recurrence of hernia. Sublay mesh repair indicates improved outcomes.